THE ROLE OF CLOUD COMPUTING TECHNOLOGY IN REDUCING PRODUCT DEVELOPMENT AND DESIGN COSTS-AN APPLIED STUDY IN WASIT GENERAL COMPANIES FOR TEXTILE INDUSTRIES - Marwah Jumaah Tuama (Scholars Digest Publishing, 2024)
After the great industrial revolution that occurred in developed countries, the great need for technology appeared in the work of companies. several technologies have emerged, and one of these important technologies is cloud computing technology, which will have a significant impact in the field of reducing product costs. The research aims to know the extent of the role of cloud computing technology in reducing the costs of design and development. Products The importance of the research focused on identifying the concept and importance of cloud computing in industrial companies and its role in reducing product costs. The study stipulated several hypotheses and it has It was completed Choose the General Company for Textile Industries in Wasit as a sample for research And it was done Reliance on Questionnaire form Its component from Two axes40 were distributed Questionnaire And use program spss For the purpose of investigation Goals Research and verify its hypotheses Through this study, several conclusions were reached, the most important of which is the lack of application of modern technologies, the most important of which is cloud computing technology in the research sample company. The research came out with a set of recommendations, the most important of which is industrial companies adopting cloud computing technology because it helps provide many competitive advantages.
Keywords: cloud computing technology, product development and design costs.